Public Service, Performance Enhancement and the Challenge of Economic Recession in Nigeria (Journal of Management and Social Sciences, 2018)
AbstractThe Nigerian economy has just technically exited recession. This harsh economic condition is no doubt of great concern to the government and people of the country inview of its attendant pains. Economic and financial experts and professionals areexpected to find solution to this national challenge. This paper however argues that, inaddition to seeking economic solution to this problem, the nation’s public service in itsposition as the main machinery of government for the formulation and implementationof public policies should be recognised as a critical factor in exiting the country out ofrecession. This can be done by continuous training and re-training of public servants inorder to increase their competence, morale and productivity towards speedy recoveryof the country’s economy. The paper adopted the qualitative method of analysis usingmainly secondary source of data.KeywordsTraining, development, economic recession, economic recovery, performanceimprovement, training needs